FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEMISKINAN DI KABUPATEN SAMPANG, MADURA - Jufriadi, . (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
Beggary constitute multidimensi's phenomenon, defined and is measured deep a lot of trick. In most cases, beggary was measured by economic welfare terms, as propertied as and consumption. Someone is said hole in the wall if it lies under minimum well-being zoom given already agree. Usufruct analyze can be known that t ingkat is accepted income beggary at Lacquer Regency experiences one decrease of year go to year. Of research result is known on 10 poverty the last year at Regency Lacquer experiences sizable decrease. At year 2004 total one 333.984 person, indigent population at year 2013 as 252.430 person. It figures to happen repair at Regency Lacquer in term tacling problem beggary. Available influence among population, Economic growth and SMA'S Grad Amount onto to beggary at Lacquer Regency. Proportionate islandic growth straight to beggary, its mean the greater its resident growth therefore the greater too total indigent society at Regency Lacquer. Meanwhile economic growth and SMA'S grad Population onto proportionate reverse with poverty. The greater economic growth runaway speed and SMA'S grad amount onto therefore potentially reduces to foot up society hole in the wall at Lacquer Regency.